Integrating Prospective Scenarios in Life Cycle Engineering: Case Study of Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Energies)
Lightweight design is a common approach to reduce energy demand in the use stage of vehicles. The production of lightweight materials is usually associated with an increase in energy demand, so the environmental impacts of lightweight structures need to be assessed holistically using a life cycle assessment. To estimate the life cycle environmental impacts of a product in its developmental stage, for example, by life cycle engineering, future changes in relevant influencing factors must be considered. Prospective life cycle assessment provides methods for integrating future scenarios into life cycle assessment studies. However, approaches for integrating prospective life cycle assessment into product development are limited. The objective of this work is to provide the methodological foundation for integrating future scenarios of relevant influencing factors in the development of lightweight structures. The applicability of the novel methodology is demonstrated by a case study of a structural component in a steel, aluminium, and hybrid design. The results show that appropriate decarbonisation measures can reduce the life cycle greenhouse gas emissions by up to 95 percent until 2050. We also found that shifts in the environmentally optimal design are possible in future scenarios. Therefore, the methodology and data provided contribute to improved decision-making in product development.
Keywords: Life Cycle Engineering; Life Cycle Assessment; Lightweight Design; Prospective LCA; Future-oriented LCA; Energy System; Material production; Sustainable production

Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Guideline for the dependability-oriented design of self-optimizing systems - Sondermann-Wölke, Christoph; Hemsel, Tobias; Sextro, Walter; Gausemeier, Jürgen; Pook, Sebastian (Industrial Informatics (INDIN), 2010 8th IEEE International Conference on)
Self-optimizing systems are able to adapt their behavior autonomously according to their current self-determined objectives. Unforeseen influences could lead to dependability-critical behavior of the system. Methods are required which secure self-optimizing systems during operation. These methods to increase the dependability of the system should already be taken into consideration in the design process. This paper presents a guideline for the dependability-oriented design of self-optimizing systems, which integrates established classical methods like failure mode and effects analysis as well as methods based on self-optimization. On the one hand self-optimization is used to increase the dependability of the system by integrating objectives like safety, availability, and reliability to the objectives of the system. On the other hand methods are required to ensure the self-optimization itself. As basis for this guideline serves the principle solution of the system. The six phases of the guideline extend the design process and lead to an enhanced principle solution. Additionally, the guideline illustrates phases to implement and validate the self-optimizing system. The proposed guideline is applied to an innovative rail-bound vehicle, called RailCab, which is equipped with self-optimizing function modules.
Keywords: RailCab; dependability-critical behavior; dependability-oriented design; failure mode; rail-bound vehicle; secure self-optimizing systems; self-optimizing function modules; optimisation; railways; self-adjusting systems

A Systematic Approach to Combined HW/SW System Test - Krupp, Alexander; Müller, Wolfgang (Proceedings of DATE’10)
Today we can identify a big gap between requirement specification and the generation of test environments. This article extends the Classification Tree Method for Embedded Systems (CTM/ES) to fill this gap by new concepts for the precise specification of stimuli for operational ranges of continuous control systems. It introduces novel means for continuous acceptance criteria definition and for functional coverage definition.
Keywords: System testing; Automatic testing; Object oriented modeling; Classification tree analysis; Automotive engineering; Mathematical model; Embedded system; Control systems; Electronic equipment testing; Software testing

Children's lexical skills and task demands affect gestural behavior in mothers of late-talking children and children with typical language development - Grimminger, Angela; Rohlfing, Katharina; Stenneken, Prisca (Gesture)
Keywords: task- oriented dialogue; Late Talker; maternal multimodal input; gestural motherese

Online Diarization of Streaming Audio-Visual Data for Smart Environments - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (IEEE Journal of Selected Topics in Signal Processing)
For an environment to be perceived as being smart, contextual information has to be gathered to adapt the system's behavior and its interface towards the user. Being a rich source of context information speech can be acquired unobtrusively by microphone arrays and then processed to extract information about the user and his environment. In this paper, a system for joint temporal segmentation, speaker localization, and identification is presented, which is supported by face identification from video data obtained from a steerable camera. Special attention is paid to latency aspects and online processing capabilities, as they are important for the application under investigation, namely ambient communication. It describes the vision of terminal-less, session-less and multi-modal telecommunication with remote partners, where the user can move freely within his home while the communication follows him. The speaker diarization serves as a context source, which has been integrated in a service-oriented middleware architecture and provided to the application to select the most appropriate I/O device and to steer the camera towards the speaker during ambient communication.
Keywords: audio streaming; audio visual data streaming; context information speech; face identification; face recognition; image segmentation; middleware; multimodal telecommunication; online diarization; service oriented middleware architecture; sessionless telecommunication; software architecture; speaker identification; speaker localization; speaker recognition; steerable camera; telecommunication computing; temporal segmentation; terminal-less telecommunication; video streaming

OFDM Channel Estimation Based on Combined Estimation in Time and Frequency Domain - Haeb-Umbach, Reinhold; Bevermeier, Maik (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2007))
In this paper we present a novel channel impulse response estimation technique for block-oriented OFDM transmission based on combining estimators: the estimates provided by a Kalman filter operating in the time domain and a Wiener filter in the frequency domain are optimally combined by taking into account their estimated error covariances. The resulting estimator turns out to be identical to the MAP estimator of correlated jointly Gaussian mean vectors. Different variants of the proposed scheme are experimentally investigated in an EEEE 802.11a-like system setup. They compare favourably with known approaches from the literature resulting in reduced mean square estimation error and bit error rate. Further, robustness and complexity issues are discussed
Keywords: bit error rate; block-oriented OFDM transmission; channel estimation; channel impulse response estimation; combining estimators; error statistics; frequency domain estimation; Gaussian mean vectors; Gaussian processes; Kalman filter; Kalman filters; MAP estimator; maximum likelihood estimation; OFDM channel estimation; OFDM modulation; time domain estimation; time-frequency analysis; Wiener filter; Wiener filters

A Model-Based Approach for Executable Specification on Reconfigurable Hardware - Schattkowsky, Tim; Müller, Wolfgang; Rettberg, Achim (Proceedings of DATE’05)
UML 2.0 provides a rich set of diagrams for systems documentation and specification. Much effort has been undertaken to employ different aspects of UML for multiple domains, mainly in the area of software systems. Considering the area of electronic design automation, however, we currently see only very few approaches which investigate UML for hardware design and hardware/software co-design. We present an approach for executable UML closing the gap from system specification to its model-based execution on reconfigurable hardware. For this purpose, we present our abstract execution platform (AEP), which is based on a virtual machine running an executable UML subset for embedded software and reconfigurable hardware. This subset combines UML 2.0 classes, state-machines and sequence diagrams for a complete system specification. We describe how these binary encoded UML specifications can be directly executed and give the implementation of such a virtual machine on a Virtex II FPGA. Finally, we present evaluation results comparing the AEP implementation with C code on a C167 microcontroller.
Keywords: Hardware; Unified modeling language; Virtual machining; Object oriented modeling; Field programmable gate arrays; Java; Microcontrollers; Embedded software; Real time systems; Documentation

Visual Specification, Modeling, and Illustrations of Complex Systems - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang (Proceedings of HICSS-32)
This article introduces and discusses different innovative means for visual specification and animation of complex concurrent systems. It introduces the completely visual programming language Pictorial Janus (PJ) and its application in the customer-oriented design process. PJ implements a completely visual programming language with inherent animation facilities. The article outlines the transformation of purely visual PJ programs into textual imperative programming languages. The second part of the article investigates animated 3D-presentations and introduces a novel approach to an animated 3D programming language for interactive customer-oriented illustrations.
Keywords: Animation; Computer languages; Object oriented modeling; Collaboration; Process design; Graphical user interfaces; Jacobian matrices; Standardization; Feedback; Software prototyping